The legacy of neoliberalism and the rise of the extreme Right - Martin Kronauer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The paper directs attention to the rise of the extreme Right in the context of political and social changes within European societies during the last forty years. This brings the legacy of neoliberalism into focus. The author holds that neoliberalism and the rise of the extreme Right are linked in two ways: neoliberalism in itself is an antidemocratic and socially destructive political project, and by undermining social foundations of citizenship, it paved the way for the extreme Right. The latter exploits social fears rooted in societies that ever more drift apart.
Keywords: E65; F66; F68; 330; Neoliberalism; policy; inequality; citizenship; extreme Right